Measurable and Non Measurable in Architecture: 3 case studies of the Non Linear Solutions Unit - Tiazzoldi, Caterina (ARCC Conference Repository, 2019)
In the last fifteen years architecture’s frequent use of complex digital design instruments, such as algorithms, dynamic relationships, parametric systems, mapping, morphogenesis, cellular automata and bifurcation with broken symmetry, clearly shows how contemporary thinking in mathematics and physical sciences has changed the way we think about design. The incorporation of dynamics, nonlinear systems, chaos theory, emergent properties, resilience, etc., has altered our perception of the life of today’s cities. The pilot model, Applied Responsive Devices (ARD), is a methodological approach formulated to question how the change of paradigm affects the decision-making of designers. ARD has been developed within the context of the Nonlinear Solutions Unit (NSU) at Columbia University’s Architecture School. The purpose of NSU is to analyse the impact of the change of paradigm in architectural research and to consolidate research in the field of complex systems in architecture. It questions how to enhance the organisation and transfer of architectural knowledge by activating a strong interaction between analogue and digital modelling. ARD’s role is to embed sets of constraints within the modelling process that affect the decision-making of the designer. The innovation includes the way in which quantitative and qualitative parameters (i.e. social, physical, sensorial, cultural and economic) are aggregated in order to emphasise the concept of formal adaptation. Some architectural problems can be managed with a classifier system consisting of a set of rules, each of which performs particular actions every time its conditions are satisfied by a specific informational attribute. By taking into account the experimentations developed in the field of cognitive sciences (Holland, 1992), the methods contained in this proposal investigate the existing relationships between the perception of a specific reality and its translation into a set of elements that can be manipulated through computerised models.